PENGUATAN KARAKTER RELIGIUS PESERTA DIDIK SEBAGAI PONDASI MENGHADAPI TANTANGAN ABAD KE 21 DI SD NEGERI CILAKU - Leviana Ayu; Istinganatul Ngulwiyah; M. Taufik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This research is based on the urgency of instilling character education in students according to the rules set by the government. The purpose of this study was to describe the strengthening of religious character education for students in elementary schools by compiling routine programs of religious habituation. This study used a descriptive qualitative approach, where the data obtained in this study were obtained by researchers using data collection techniques such as interviews, observation, and documentation. The subjects in this study were class V participants at SD Negeri Cilaku, Curug District. The results of the study show that strengthening the religious character of students can be done by providing religious habituation to students, habituation activities can place students as something special that can train them to have good habits inherent in everyday life. The challenges of implementing the strengthening of students' religious character education can be seen from various aspects, namely (1) the teacher's knowledge of the concept of character education itself; (2) the toughest challenges are within the students, not to mention limited supervision from the teacher and the lack of supervision of students from their parents is also a challenge; (3) the school principal's policies and inadequate facilities and infrastructure are obstacles for schools in maximizing the implementation of religious character education for students. The religious character of students can be seen from their relationship with God (hablum minallah), where this can be seen from the obedience, faith, and piety of students. Meanwhile, in relation to other individuals and the environment (hablum minannas) it can be seen from the religious sub-values ​​developed by the 2017 Indonesian Ministry of Education and Culture's PKK Compilation Team.